Inside Debt Financing Theory, Practice, and Regulatory Approaches - POMELLI, ALESSANDRO (Collana del Dipartimento di Sociologia e Diritto dell'Economia Università di Bologna, 2023)
Debt finance raised from corporate insiders has attracted the attention of legal scholars over the past several years. Such an interest comes as no surprise. The variety of legal treatments reserved for insider loans across Europe, the United States and in other jurisdictions attests to an intriguing absence of any regulatory uniformity despite similar financing patterns. After reviewing the literature on the benefits and costs of inside debt financing and illustrating the diverse regulatory approaches adopted by prominent jurisdictions, the book reassesses the risk of opportunistic insider lending based on the state of a company's finances. In doing so, the book sheds light on the net costs associated with financially sound firms issuing senior debt, whether secured or unsecured, to their insiders and, by contrast, the net benefits of allowing insiders to make senior unsecured loans to firms that are in or near insolvency. Following the reexamination of the benefits and costs of insider lending, novel requirements are recommended for an efficient and fair legal response to inside debt as a source of funding for both solvent firms and financially-distressed ones.